PENGARUH BUDAYA ORGANISASI, BEBAN KERJA, KOMPENSASI, STRES KERJA DAN TURNOVER TERHADAP KINERJA KARYAWAN PT. JALUR NUGHRAHA EKAKURIR (JNE) CABANG KOTA CILACAP - Purnama, Tegar Vaisar; Adi Susanto (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of organizational culture, workload, compensation, work stress, and turnover on employee performance at PT. Jalur Nugraha Ekakurir (JNE) Cilacap Branch. This research employs a quantitative approach with a survey method. The sample consisted of permanent employees selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS. The findings reveal that, partially, organizational culture, compensation, and work stress significantly affect employee performance, while workload and turnover do not have a significant effect. Simultaneously, all five variables have a significant impact on employee performance. Therefore, improving employee performance can be achieved by strengthening organizational culture, providing appropriate compensation, and managing work stress effectively.